Faktor-faktor yang Memengaruhi Keputusan Pembelian Buket Bunga di Pasar Bunga Kalisari Semarang - Larasati, Intan; Setiadi, Agus; Prasetyo, Edy (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
This research aims to analyze the influence of product quality, service quality, income, price, consumer preferences, and parking location on the decision to purchase flower bouquets at Kalisari Flower Market in Semarang. The research method used is a survey method, and the data collection methods include interviews and observations. Respondents standardized as samples in this study are consumers who have purchased flower bouquets at Kalisari Flower Market in Semarang. The sampling method used is accidental sampling, based on the coincidence of consumers buying flower bouquets at the market location. The calculated sample size using the Lemeshow formula is 100 respondents. The data analysis methods used are descriptive analysis and multiple linear regression analysis. The study indicates that the characteristics of respondents include: on average, consumers are aged 21-30 years, predominantly female, with the dominant highest education being high school, income dominated in the range of IDR 1,500,000 - IDR 2,500,000 per month, and the average consumer purchasing frequency is ≥ 3 times in the last year. Based on the t-test results, product quality and price partially have a significant influence on the decision to purchase flower bouquets, while service quality, income, consumer preferences, and parking location do not significantly affect the decision to purchase flower bouquets at Kalisari Flower Market in Semarang. The product quality variable has the largest contribution to the purchasing decision. This means that better product quality is associated with an increased decision to purchase flower bouquets at Kalisari Flower Market in Semarang. The coefficient of determination (R2) test results yield an Adjusted R Square value of 0.468.